Reflux Nephropathy and Vesico-Ureteric Reflux in Children - Radionuclide Technique - Kemas Firman (Indonesian Pediatric Society Publishing House, 2019)
Reflux nephropathy is defined as 'renal scarring' associated with vesica-ureteral reflux (VUR) and consists of calyceal clubbing or deformity with overlying corticomedullary scarring. The older terms chronic pyelonephritis and chronic atrophic pyelonephritis should be strictly defined as a persistent or recurrent bacterial infection of the kidney involving the renal parenchyma and the pelvi-calyceal system with exudation of inflammatory cells.